2x(x-y)+y(y-x)=(2x+y)(x-y)

Simple and best practice solution for 2x(x-y)+y(y-x)=(2x+y)(x-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x-y)+y(y-x)=(2x+y)(x-y) equation:


Simplifying
2x(x + -1y) + y(y + -1x) = (2x + y)(x + -1y)
(x * 2x + -1y * 2x) + y(y + -1x) = (2x + y)(x + -1y)

Reorder the terms:
(-2xy + 2x2) + y(y + -1x) = (2x + y)(x + -1y)
(-2xy + 2x2) + y(y + -1x) = (2x + y)(x + -1y)

Reorder the terms:
-2xy + 2x2 + y(-1x + y) = (2x + y)(x + -1y)
-2xy + 2x2 + (-1x * y + y * y) = (2x + y)(x + -1y)
-2xy + 2x2 + (-1xy + y2) = (2x + y)(x + -1y)

Reorder the terms:
-2xy + -1xy + 2x2 + y2 = (2x + y)(x + -1y)

Combine like terms: -2xy + -1xy = -3xy
-3xy + 2x2 + y2 = (2x + y)(x + -1y)

Multiply (2x + y) * (x + -1y)
-3xy + 2x2 + y2 = (2x * (x + -1y) + y(x + -1y))
-3xy + 2x2 + y2 = ((x * 2x + -1y * 2x) + y(x + -1y))

Reorder the terms:
-3xy + 2x2 + y2 = ((-2xy + 2x2) + y(x + -1y))
-3xy + 2x2 + y2 = ((-2xy + 2x2) + y(x + -1y))
-3xy + 2x2 + y2 = (-2xy + 2x2 + (x * y + -1y * y))
-3xy + 2x2 + y2 = (-2xy + 2x2 + (xy + -1y2))

Reorder the terms:
-3xy + 2x2 + y2 = (-2xy + xy + 2x2 + -1y2)

Combine like terms: -2xy + xy = -1xy
-3xy + 2x2 + y2 = (-1xy + 2x2 + -1y2)

Add '-2x2' to each side of the equation.
-3xy + 2x2 + -2x2 + y2 = -1xy + 2x2 + -2x2 + -1y2

Combine like terms: 2x2 + -2x2 = 0
-3xy + 0 + y2 = -1xy + 2x2 + -2x2 + -1y2
-3xy + y2 = -1xy + 2x2 + -2x2 + -1y2

Combine like terms: 2x2 + -2x2 = 0
-3xy + y2 = -1xy + 0 + -1y2
-3xy + y2 = -1xy + -1y2

Solving
-3xy + y2 = -1xy + -1y2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'xy' to each side of the equation.
-3xy + xy + y2 = -1xy + xy + -1y2

Combine like terms: -3xy + xy = -2xy
-2xy + y2 = -1xy + xy + -1y2

Combine like terms: -1xy + xy = 0
-2xy + y2 = 0 + -1y2
-2xy + y2 = -1y2

Add '-1y2' to each side of the equation.
-2xy + y2 + -1y2 = -1y2 + -1y2

Combine like terms: y2 + -1y2 = 0
-2xy + 0 = -1y2 + -1y2
-2xy = -1y2 + -1y2

Combine like terms: -1y2 + -1y2 = -2y2
-2xy = -2y2

Divide each side by '-2y'.
x = y

Simplifying
x = y

See similar equations:

| 1x-1y+1= | | 2/X=13/52 | | 2a(a-2x)+y(a-2x)+(a-2x)=(2a+y+1)(a-2x) | | 8x-24=x | | X^3+15=25 | | 6u-4u=18 | | 500x+200(8-x)=220 | | -3-(11/8) | | 2(2x+3)=6x-1 | | x^4-x^2-x=0 | | (-1/2-7/8) | | 4x+20=-2x-6 | | -6(x-7)=84 | | (-1/2)-(7/8) | | Y=1/5wx | | 2(6a+8)=100 | | (0.0625x^2)+(0.25x)+1=0 | | (0.16666666666666666x^2)+(0.25x)+1=0 | | x*2=200+169 | | 9^(3x)=((3^x)^x)/(3^7) | | -3(7r+8)=100 | | 8a+10b=73 | | -258=7(1+8r)-3r | | 4y+10=2y+7 | | 60/1=x/2.05 | | 1-8(1+8p)=249 | | 6x+2y+4z=z | | 2+7(5m+1)=219 | | 4c+3d-2c+2d= | | 5m+6.75=49.25 | | 132=-6(5n-2) | | (0.25x^2)+(0.25x)+1=0 |

Equations solver categories